2008
DOI: 10.1002/elps.200700519
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for analysis of oligonucleotide–cisplatin interactions by continuous elution gel electrophoresis coupled to isotope dilution inductively coupled plasma mass spectrometry and matrix‐assisted laser desorption/ionization mass spectrometry

Abstract: In this work we present a novel approach for in vitro studies of cisplatin interactions with 8-mer oligonucleotides. The approach is based on the recently developed coupling of continuous elution gel electrophoresis (GE) to an inductively coupled plasma-sector field mass spectrometer (ICP-SFMS) with the aim of monitoring the interaction process between this cytostatic drug and the nucleotides. In contrast to existing methods, the electrophoretic separation conditions used here allow both the determination of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Although the determination of phosphorus in a DNA molecule using ICP‐MSor ICP‐optical emission spectrometry (OES) has been recognized as an accurate DNA quantification, the determination results only show the total amount of DNA in the sample . Therefore, hyphenated techniques such as LC or electrophoresis with ICP‐MS are considered useful analytical tools . We have reported the coupling techniques of LC with ICP‐MS, where we employed RP chromatography only for the analysis of mono‐nucleotides was performed .…”
Section: Results From Analysis Of Nmij Crm 6204‐a By the Proposed Meamentioning
confidence: 99%
“…Although the determination of phosphorus in a DNA molecule using ICP‐MSor ICP‐optical emission spectrometry (OES) has been recognized as an accurate DNA quantification, the determination results only show the total amount of DNA in the sample . Therefore, hyphenated techniques such as LC or electrophoresis with ICP‐MS are considered useful analytical tools . We have reported the coupling techniques of LC with ICP‐MS, where we employed RP chromatography only for the analysis of mono‐nucleotides was performed .…”
Section: Results From Analysis Of Nmij Crm 6204‐a By the Proposed Meamentioning
confidence: 99%
“…The interaction of cisplatin and guanosine monophosphate was also studied by Hann et al 395 They found mono-and biadducts, which were separated from one another by HPIC and analysed for of 31 396 The artificial oligonucleotides contained either adjacent guanosines (GG) or not (TG). Mono-and biadducts were detected and the respective binding constants could be determined.…”
Section: Element-specific Detection Of Small Molecules In Biological mentioning
confidence: 97%
“…CE offers the possibility of investigating the interaction under conditions corresponding to physiological conditions (aqueous media, pH, and temperature) and is valuable for such studies [146,149,[167][168][169][170][171][172]. Gel electrophoresis coupled with ICP MS and MALDI TOF MS has proved useful for examination of the interaction of cisplatin with oligonucleotides [173].…”
Section: Determination Of Platinum In Clinical Samplesmentioning
confidence: 99%